Enhanced visualizing charge distribution of 2D/2D MXene/MoS2 heterostructure for excellent microwave absorption performance - Li, Xiao; Wen, Caiyue; Yang, Liting; Zhang, Ruixuan; Li, Yuesheng; Che, Renchao (Journal of alloys and compounds, 2021)
•2D/2D MXene/MoS2 heterostructure was successfully prepared by a facile hydrothermal method.•Visualizing charge distribution was firstly characterized at 2D interface by electron holography.•The synergistic effects between two different 2D materials is detailed analyzed.•The MXene-MoS2 composites exhibit the excellent MA performance (RL= -46.72 dB, EAB =4.32 GHz). The MXene-MoS2 composite with massive 2D/2D heterostructures holds the excellent microwave absorption performance accompanied by the superior RL (−46.72 dB) and the distinct EAB (4.32 GHz) at only 2 mm thickness. [Display omitted] The unique 2D/2D heterostructures can fully combine their respective 2D properties and exhibit enhanced performance due to its synergistic effect. However, how to effectively introduce other foreign 2D materials on the 2D MXene substrate, as well as research on their detailed synergistic effects, is still in lack. Herein, 3D conductive interconnected network with massive 2D/2D heterostructures in MXene-MoS2 composites are constructed by a facile hydrothermal reaction, and the microwave absorption mechanism accompanying the synergistic effect is detailed analyzed. Impressively, the unique off-axis electron holography is firstly used to visually characterize the distribution of charge density at the 2D interface, which constructs an effective relationship between the charge density distribution at the 2D/2D heterostructures and the strength of the microwave absorption performance. In addition, the confined space provided by each independent accordion-like multilayered MXene facilitates the heterogeneous coupling between the layers to increase its dielectric loss capability. Accordingly, the MXene-MoS2 composite holds the excellent microwave absorption performance accompanied by the superior reflection loss (RL) (−46.72 dB) and the distinct effective absorption bandwidth (EAB) (4.32 GHz) at only 2 mm thickness. This work refers an archetype for studying the synergistic effect between 2D/2D heterostructures.